THE ESSENCE OF QUESTIONING AND EXPLICIT READING INSTRUCTION STRATEGY - Muzamil, Sa'adullah (Universitas Islam Negeri Raden Intan Lampung, 2013)
Teacher‟s questioning may function to assist students comprehend more readingmaterials and to enable them to be proficient readers. Yet, the students may beless benefited from which if the teacher neither provides sufficient explicit readingstrategy nor involves higher-level questions. Consequently, the teacher should paymore careful attention on the followings: 1) the teacher should involve bothlower-, and higher-level questions; 2) the teacher should equip students withexplicit reading strategy; 3) the teacher should be aware of the activities should beexecuted in reading phases: pre-, during-, and post-reading.